Zora's Bookshelf in The Quest of the Silver Fleece by W. E. B. Du bois. Issue 3 (2nd October 2019) - Withun, David
Abstract: W. E. B. Du Bois frequently wrote lists of books that he recommended others to read. One of the most intriguing of these lists occurs in his 1911 novel The Quest of the Silver Fleece . As the hero Bles scans the bookshelf of the heroine Zora, he notes six works or collections of works by name: Plato's Republic, Gorky's Comrades, an encyclopedia of agriculture, Balzac's novels, Spencer's First Principles, and Tennyson's poetry. This essay briefly examines these works and the possible significance of each in the light of Du Bois's ideas, such as the doctrine of the "Talented Tenth, " the need for intraracial solidarity among African Americans, Pan-Africanism, and others, as well as the role that the ideas of each of these works may play in the wider context of the novel. Each seems to be representative of some significant aspect of the communal agricultural philosophy of Zora, which, in turn, reflects some of the foundational philosophical commitments of Du Bois himself.